Characterization and sequence analysis of the scrA gene encoding enzyme IIScr of the Streptococcus mutans phosphoenolpyruvate-dependent sucrose phosphotransferase system. - Sato, Y (1989)
The Streptococcus mutans GS-5 scrA gene coding for enzyme IIScr of the phosphoenolpyruvate-dependent sucrose phosphotransferase system (PTS) was localized upstream from the scrB gene coding for sucrose-6-phosphate hydrolase activity after Mu dE transposon mutagenesis of plasmid pMH613. The cloned scrA gene product was identified as a 68-kilodalton protein by minicell analysis after isolation of the gene in plasmid pD4. In addition, the membrane fraction from Escherichia coli cells containing pD4 exhibited sucrose PTS activity upon complementation with enzyme I and HPr from strain GS-5. The nucleotide sequence of the scrA region revealed that this gene was located immediately upstream from the scrB gene and divergently transcribed from the opposite DNA strand. The scrA gene was preceded by potential Shine-Dalgarno and promoterlike sequences and was followed by a transcription terminator-like sequence. The scrA gene coded for an enzyme IIScr protein of 664 amino acid residues with a calculated molecular weight of 69,983. This enzyme IIScr protein was larger than the comparable proteins from Bacillus subtilis and E. coli containing sucrose-metabolizing plasmid pUR400. The 491-amino-acid N-terminal sequence of the S. mutans enzyme IIScr was homologous with the B. subtilis and E. coli sequences, and the 173-amino-acid C-terminal sequence of the S. mutans protein was also homologous with the Salmonella typhimurium enzyme IIIGlc and the 162-amino-acid C terminus of E. coli enzyme IIBgl. These results suggest that the sucrose PTS system of S. mutans is enzyme III independent.